Pengaruh Kecerdasan Emosional Dan Kecerdasan Intelektual Terhadap Tingkat Pemahaman Dasar Akuntansi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Sumatera Utara - irfan irfan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
tecnhiques in this study, the questionnaire and data analysis tecnhiques in this analysis are multiple regression analysis. Hypothesis testing results show that the value of t count emotional intelligence variables to the level of accounting basic understanding of 6.068 compared to the value of t table 1.65251 means 6.068>1.65351 which means that emotional intellegence variables have an influence on the level of basic understanding of accounting in students of economic and business faculty Muhammadiyah Sumatra. Hypothesis testing results show that the value of the intellectual intelligence variable to the level of accounting basic understanding is -710 compared to the value of t table 1.65251 means 0.710< 1.65251 which means that intellectual intelligence variables do not influence the level of basic understanding of accounting in students of economic faculty and business of muhammadiyahuniversity of north sumatra. As for results of testing the hypothesis it is known that there is a simultaneous influence of emotional intelligence and intellectual intelligence together on the level of basic understanding of accounting in students of faculty of economics and business at muhammadiyah university in north sumatra, where the value of f count = 18.551>f table 3.85 means Ha is accepted and Ho rejected.